Krajobraz i nacjonalizm. Baskijski pejzaż narodowy - Mirgos, Katarzyna (Studia Europaea Gnesnensia, 2011)
The article addresses the issue of ideological exploitation of the landscape, of making into an ethnolandscape, which is an important element of the nationalist thought. The authoress analyses the question on the example of the Basque culture, discussing the meaning or the territory and home in the Basque worldview, the most important elements of the Basque national landscape and the way in which they are created and preserved (art, literature).